Perceptions de la migration interprovinciale des Canadiens anglais et Canadiens pour la vitalité des Québécois, Acadiens et Franco-ontariens - Bourhis, Richard Y.; Sioufi, Rana (2022)

Anglophone and Francophone Desire to Stay or Leave Quebec : A Study of Quebec-born Undergraduates in Montreal - Bourhis, Richard Y.; Sioufi, Rana (The Charter : Bill 101 and English-Speaking Quebec/La Charte : La loi 101 et les Québécois d’expression anglaise, 2021)

L'exode des jeunes anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Keywords: Official Language Minority Community (OLMC)

Outmigration of Quebec's English-speaking Youth - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Keywords: Official Language Minority Community (OLMC)

Working Papers on English Language Institutions in Quebec - Schachter, Susan (Alliance Quebec (AQ), 1982)
This project was designed to provide a resource for Quebec's English-speaking community and others who feel the need for information about themselves and those institutions usually identified as "English". The decision that such a resource was needed was based on both objective and subjective criteria. Objectively, the English-speaking population of Quebec is, and always has been, an unstable one; that is, large numbers of English-speaking people have always been among those moving to and from the province, Ieaving behind a relatively small core of their fellows with deep roots in Quebec. This high turn-over in population has affected the continuity of the English-speaking community. Such a state of fluidity has made it difficult to evolve a distinctive English-speaking cultural identity with Quebec as its focal point. On the other hand, it has Ied to a discontinuity in the knowledge of our economic, political and cultural role in Quebec. Hence, the need for a resource such as this.